CHSSN Montreal Community Forum : Mental Health and COVID-19 - Community Health and Social Services Network (CHSSN) (2021)
The forum brought together representatives from the provincial government, the health sector, the community, various research initiatives, and leaders from across the Island of Montreal to discuss the effects of COVID-19 on mental health for English speakers living on the Island. The event also served as a platform forcelebrating the successes of different mental health initiatives and for co-generating solutions to some of the most urgent problems facing mental health amongst English speakers in the context of COVID-19. With the goal of deepening an understanding of the impact of COVID-19 on different demographic segments of the English-speaking population of Montreal, CHSSN invited speakers working with a wide range of populations and possessing diverse lived experiences of the pandemic. The forum was designed to foster cross-sectoral and intersectional exchanges and to create a space for learning, discovery, consciousness-raising, resource-sharing, networking, and collaborating.

Reisaction : Our Response to Covid-19 - Réseau de l’est de l’île pour les services en anglais (REISA) (2020)